Water balance complexities in ephemeral catchments with different land uses: Insights from monitoring and distributed hydrologic modeling. Issue 6 (19th June 2016) - Dean, J. F.; Camporese, M.; Webb, J. A.; Grover, S. P.; Dresel, P. E.; Daly, E.
Abstract: Although ephemeral catchments are widespread in arid and semiarid climates, the relationship of their water balance with climate, geology, topography, and land cover is poorly known. Here we use 4 years (2011–2014) of rainfall, streamflow, and groundwater level measurements to estimate the water balance components in two adjacent ephemeral catchments in south‐eastern Australia, with one catchment planted with young eucalypts and the other dedicated to grazing pasture. To corroborate the interpretation of the observations, the physically based hydrological model CATHY was calibrated and validated against the data in the two catchments. The estimated water balances showed that despite a significant decline in groundwater level and greater evapotranspiration in the eucalypt catchment (104–119% of rainfall) compared with the pasture catchment (95–104% of rainfall), streamflow consistently accounted for 1–4% of rainfall in both catchments for the entire study period. Streamflow in the two catchments was mostly driven by the rainfall regime, particularly rainfall frequency (i.e., the number of rain days per year), while the downslope orientation of the plantation furrows also promoted runoff. With minimum calibration, the model was able to adequately reproduce the periods of flow in both catchments in all years. Although streamflow and groundwater levels were better reproduced in the pasture than in the plantation, model‐computed water balance terms confirmed the estimates from the observations in both catchments. Overall, the interplay of climate, topography, and geology seems to overshadow the effect of land use in the study catchments, indicating that the management of ephemeral catchments remains highly challenging. Key Points: Four‐year catchment‐scale water balances of a tree plantation and pasture were compared Frequency of rainfall events appeared to be crucial in driving annual streamflow Detailed topography and geology information is key to modeling ephemeral catchment hydrology